(untitled) (Jurnal Manajemen Bisnis, 2026)
This study aims to examine the role of Dividend Policy in moderating the relationship between Liquidity, Profitability, and leverage on Company Value in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative approach with moderated regression analysis. The population in this study comprises 12 pharmaceutical companies listed on the IDX, with a sample of 6 selected through purposive sampling. Data collection was conducted using documentation methods through the company’s financial reports. Data analysis included classical assumption testing, descriptive analysis, hypothesis testing, moderation regression, and coefficient of determination using Statistical Product and Services Solutions (SPSS) software. The results of the study indicate that Dividend Policy strengthens the influence of Liquidity, Profitability, and Leverage on Firm Value. The positive relationship found indicates that the higher the level of Liquidity, Profitability, and Leverage reinforced by Dividend Policy, the higher the Company Value. This finding emphasizes the importance of dividend policy in increasing investor confidence and attracting investment, thereby increasing company value. This study contributes theoretically to the understanding of the role of Dividend Policy as a moderating variable. Practically, the results of this study can be used by pharmaceutical company managers to formulate appropriate dividend policies to increase company value and to provide guidance for investors in making investment decisions.